Sekular: Relevannya Dengan Malaysia (Secularism and its relevance With Malaysia) - Safei, Su'aidi (Terengganu State Foundation Printing, 1999)
To what extent is it relevant to the issue of secularism in Malaysia practically? Is it true that Malaysia is a secular government separating religion from country governance? The leading government in Malaysia vehemently disclaimed and denied the allegations of secularism practice and the act against Islam.